2020
DOI: 10.3389/fmicb.2020.00866
|View full text |Cite
|
Sign up to set email alerts
|

Microevolution and Gain or Loss of Mobile Genetic Elements of Outbreak-Related Listeria monocytogenes in Food Processing Environments Identified by Whole Genome Sequencing Analysis

Abstract: Whole genome sequencing (WGS) analyses have been instrumental in traceback investigations of Listeria monocytogenes (Lm). To demonstrate how long-read sequencing analysis can capture and describe relationships among isolates from clinical, food, and environmental sources, we analyzed 366 long-read-and shotgun-sequenced isolates from 16 Lm outbreak strains associated with cantaloupe, leafy green, stone fruit, caramel apple, mung bean sprout, multiple cheese products, multiple ice cream products, and their produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 52 publications
1
18
0
Order By: Relevance
“…Comparative genomics and evolutionary analysis on a small portion of prophage regions next to the phage insertion sites of the 1998 and 2002 Lm ECII outbreak isolates indicated that the prophage region might be conserved among isolates that were associated with the same outbreak, which represented a short-term evolution scenario [ 7 , 8 ]; these studies did not review the entire prophage regions. A similar phenomenon was observed in isolates from ECs associated with other listeriosis outbreaks that were linked to different types of foods when the entire prophage regions of these isolates were analyzed [ 9 ]. Thus, prophage regions might be important genetic markers to determine epidemiological relatedness and to identify resident strains.…”
Section: Introductionsupporting
confidence: 62%
See 3 more Smart Citations
“…Comparative genomics and evolutionary analysis on a small portion of prophage regions next to the phage insertion sites of the 1998 and 2002 Lm ECII outbreak isolates indicated that the prophage region might be conserved among isolates that were associated with the same outbreak, which represented a short-term evolution scenario [ 7 , 8 ]; these studies did not review the entire prophage regions. A similar phenomenon was observed in isolates from ECs associated with other listeriosis outbreaks that were linked to different types of foods when the entire prophage regions of these isolates were analyzed [ 9 ]. Thus, prophage regions might be important genetic markers to determine epidemiological relatedness and to identify resident strains.…”
Section: Introductionsupporting
confidence: 62%
“…The mutation rate on 33 CC321 strains from lineage II was 1.15 × 10 −7 (95% HPD, 0.79 × 10 −7 to 1.52 × 10 −7 ) substitutions/site/year [ 34 ]. In another study that calculated substitution rates among isolates associated with specific outbreaks, the average substitution rates were slightly higher, 5.5 × 10 −7 to 5.8 × 10 −7 substitutions/site/year for CC6 isolates associated with two different outbreaks linked to contaminated cheese products [ 9 ]. In our study, the time between the most recent common ancestor and the outbreak recognition was 30 and 52 years for the 1998 and 2002 U.S. outbreak, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such persistence is mediated by several adaptations, including the ability to form persistent biofilms, tolerance to sanitizers such as quaternary ammonium compounds, growth at low temperatures, and phage resistance (Kathariou, 2002;Gandhi and Chikindas, 2007;Kim et al, 2008;Carpentier and Cerf, 2011;Kathariou et al, 2017). The increasing employment of whole genome sequencing (WGS) has significantly facilitated the assessment of L. monocytogenes persistence in individual food processing plants, greatly improving the resolution afforded by previous tools such as pulsed-field gel electrophoresis or the seven-locus multilocus sequence typing (MLST) scheme (Fagerlund et al, 2016(Fagerlund et al, , 2020Knudsen et al, 2017;Hurley et al, 2019;Stoller et al, 2019;Harrand et al, 2020;Yang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%